Genome-Wide Integrated Analysis Revealed Functions of lncRNA–miRNA–mRNA Interaction in Growth of Intermuscular Bones in Megalobrama amblycephala - Chen, Yulong; Wan, Shiming; Li, Qing; Dong, Xiaoru; Diao, Jinghan; Liao, Qing; Wang, Gui-Ying; Gao, Ze-Xia (Frontiers in Cell and Developmental Biology, 2021)
Intermuscular bone (IB) occurs in the mosepta of teleosts. Its existing has an adversely influence on the fish edible and economic value, especially for aquaculture species belonging to Cypriniformes. The growth mechanism of IBs is quite lacking. In this study, we firstly used SMRT technology to improve the draft genome annotation and fully characterization of transcriptome for one typic aquaculture species, blunt snout bream (Megalobrama amblycephala). The lncRNA, miRNA, and mRNA expression profiles in two IB growth stages (one-year old; three-year old) were compared through transcriptome and degradome analysis. A total of 126 miRNAs, 403 mRNAs and 353 lncRNAs were found to be differentially expressed between the two stages. KEGG analysis revealed that the significantly up-regulated map2k6 and cytc in the MAPK/p53 signaling pathway and the significantly down-regulated lama3 and thbs4b in the ECM-receptor pathway may play a key regulatory role in the IB growth. Bioinformatics analysis subsequently revealed 14 ceRNA pairs related to the growth of IBs，consisting of 10 lncRNAs, 7 miRNAs and 10 mRNAs. Of them, dre-miR-24b-3p and dre-miR-193b-3p are core regulatory factors interacting with 4 lncRNAs and 3 mRNAs, which interaction mechanism was also revealed by subsequent experiments at the cellular level. In conclusion, our data showed that IBs had higher activity of cell apoptosis and lower mineralization activity in IB_III compared to IB_I via interaction of MAPK/p53 and ECM-receptor signaling pathways. The down-regulated zip1 interacted with miR-24a-3p and lnc017705 decreased osteoblast differentiation and Ca2+ deposition in IB_III stage. Our identified functional mRNAs, lncRNAs and miRNAs provide a data basis for in-depth elucidation of the growth mechanism of teleost IB.